2015
DOI: 10.2169/internalmedicine.54.3690
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Small Intestinal Endoscopy in a Case of Adult-onset Familial Mediterranean Fever Associated with Jejunoileitis

Abstract: A 66-year-old Japanese man consulted our institution due to paroxysmal and repetitive bouts of fever and abdominal pain that had persisted for more than one week. Capsule and double-balloon endoscopy (DBE) showed petal-shaped mucosal redness with white hemming in the jejunum and ileum, and histopathology of the biopsy specimens revealed villous atrophy and cryptitis with extensive severe neutrophil infiltration. A genetic examination disclosed compound heterozygous MEFV mutations (E84K, P369S), and familial Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…It was first described in 1997, and shown that mutations in the Mediterranean fever (MEFV) gene, which is found in the short arm of the 16th chromosome (16p13.3), is responsible for FMF. The disease is frequently seen in Turks, Jews, Armenians, Arabs, and Japanese [ 2 ]. More than 70 mutations have been identified in the MEFV gene and the most common mutations is M694V [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was first described in 1997, and shown that mutations in the Mediterranean fever (MEFV) gene, which is found in the short arm of the 16th chromosome (16p13.3), is responsible for FMF. The disease is frequently seen in Turks, Jews, Armenians, Arabs, and Japanese [ 2 ]. More than 70 mutations have been identified in the MEFV gene and the most common mutations is M694V [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 10 ] To date, however, only a few endoscopic findings of gastrointestinal lesions in patients with FMF have been described so far. [ 6 12 ] In the present article, we report a case of FMF in which both the clinical symptoms and endoscopic findings resembled those of CD.…”
Section: Introductionmentioning
confidence: 83%
“…Demir et al, [ 11 ] examined 41 patients with FMF by capsule endoscopy and found mucosal defects (erosions or ulcers) in the small bowel in 44% of patients. Kitade et al [ 12 ] reported a case of FMF with multiple jejunoileal lesions of petal-shaped redness and white hemming detected by capsule endoscopy and double-balloon endoscopy. Thus, patients with FMF are presumed to have variable small bowel lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Villous atrophy can occasionally be observed under endoscopic studies in patients with persistent diarrhea, especially in those suffering from inflammatory diseases of the gastrointestinal (GI) tract such as celiac disease, Crohn’s disease, eosinophilic gastroenteritis and familial Mediterranean fever [25]. Crohn’s disease and eosinophilic gastroenteritis usually show specific histological features such as intestinal granuloma and eosinophil infiltrate, respectively.…”
Section: Introductionmentioning
confidence: 99%